Optimization of rectifier circuits for a vibration energy harvesting system using a macro-fiber composite piezoelectric element. (August 2016) - Kashiwao, Tomoaki; Izadgoshasb, Iman; Lim, Yee Yan; Deguchi, Mikio
Abstract: This paper proposes an optimization method for the rectifier circuit of a vibration energy harvesting system that uses macro-fiber composite (MFC) piezoelectric elements. MFC elements have previously been investigated intensively for piezoelectric energy harvesting. A bridge rectifier circuit composed of diodes and capacitors is often used as the rectifier circuit, which functions as an AC–DC converter. In contrast, a double-voltage rectifier circuit can generate twice the voltage of the bridge rectifier. In this study, both types of rectifier circuits are optimized by varying the values of the diode forward voltages and thecapacitance of the capacitors. In addition, the current–voltage characteristic and electric power efficiency of these rectifier circuits are evaluated and compared. The experimental results show that the electric power efficiency of the bridge rectifier circuit is higher than that of the double-voltage rectifier circuit at maximum electric power; however, the double-voltage rectifier circuit is suitable foruse in high voltage situations. In addition, the use of diodes with lower forward voltages leads to higher electric power efficiency, but the capacitance of the capacitors has no effect on electric power efficiency.